2016
DOI: 10.1515/jvetres-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

First report of Leptospira infections in red deer, roe deer, and fallow deer in Poland

Abstract: Introduction: Recently in Europe an increase in the population of red deer (Cervus elaphus), roe deer (Capreolus capreolus), and fallow deer (Dama dama) has been observed. Research on the prevalence of Leptospira infections in Polish cervids has been performed for the first time. Material and Methods: During 2014/2015 hunting season, 147 blood samples from red deer, roe deer, and fallow deer were collected. The animals originated from different geographical regions across Poland. Serum samples were tested by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Antibodies against serovar Pomona (42.8%) were detected most frequently. The seroprevalence of antibodies against leptospiral serovars found in this study was significantly higher than that in Italy (6.33%) [ 17 ] or in Poland, which showed a total seroprevalence in deer (roe deer, red deer and fallow deer) of 4.8% [ 74 ], or in Croatia (19.02%) [ 42 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Antibodies against serovar Pomona (42.8%) were detected most frequently. The seroprevalence of antibodies against leptospiral serovars found in this study was significantly higher than that in Italy (6.33%) [ 17 ] or in Poland, which showed a total seroprevalence in deer (roe deer, red deer and fallow deer) of 4.8% [ 74 ], or in Croatia (19.02%) [ 42 ].…”
Section: Discussionmentioning
confidence: 67%
“…Antibodies against serovar Icterohaemorrhagiae (65%) were most frequently detected. The seroprevalence of antibodies against leptospiral serovars found in this study was considerably higher than that in Croatia (6.0%) [ 42 ] or in Poland, which showed an overall seroprevalence in deer (roe deer, red deer and fallow deer) of 4.8% [ 74 ], or in Germany (2%) [ 75 ]. No positive serological reactions were found in roe deer ( n = 66) in Italy [ 17 ].…”
Section: Discussionmentioning
confidence: 74%
“…Previous experience has shown that small mammals were leading sources of leptospirosis (Badra 2008, Żmudzki et al 2016). A total of 2820 small mammals were collected and tested by MAT (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…and is considered a potential source of leptospires, which then infect humans and domestic animals. An increase in the population density of wild boar has been documented in many European countries, including Italy (5,13,24), and a consequential increase in potential interactions among wild boar, humans, domestic animals, and other wildlife species could increase the dissemination risk of such a disease (19). We suggest that wild boar, pigs, and dogs within the grazing range should be evaluated for potential risks of transmission that they may pose and that co-grazing (particularly with pigs) should be avoided.…”
Section: Discussionmentioning
confidence: 99%